Epidemiology and Outcomes of Critically Ill Children at Risk for Pediatric Acute Respiratory Distress Syndrome: A Pediatric Acute Respiratory Distress Syndrome Incidence and Epidemiology Study*. Issue 3 (27th September 2021) - Shein, Steven L.; Maddux, Aline B.; Klein, Margaret J.; Bhalla, Anoopindar; Briassoulis, George; Dahmer, Mary K.; Emeriaud, Guillaume; Flori, Heidi R.; Gedeit, Rainer; Ilia, Stavroula; Kneyber, Martin C. J.; Napolitano, Natalie; et al.
Abstract : OBJECTIVES: Interventional trials aimed at pediatric acute respiratory distress syndrome prevention require accurate identification of high-risk patients. In this study, we aimed to characterize the frequency and outcomes of children meeting "at risk for pediatric acute respiratory distress syndrome" criteria as defined by the Pediatric Acute Lung Injury Consensus Conference. DESIGN: Planned substudy of the prospective multicenter, international Pediatric Acute Respiratory Distress Syndrome Incidence and Epidemiology study conducted during 10 nonconsecutive weeks (May 2016–June 2017). SETTING: Thirty-seven international PICUs. PATIENTS: Three-hundred ten critically ill children meeting Pediatric Acute Lung Injury Consensus Conference "at-risk for pediatric acute respiratory distress syndrome" criteria. INTERVENTIONS: None. MEASUREMENTS AND MAIN RESULTS: We evaluated the frequency of children at risk for pediatric acute respiratory distress syndrome and rate of subsequent pediatric acute respiratory distress syndrome diagnosis and used multivariable logistic regression to identify factors associated with subsequent pediatric acute respiratory distress syndrome. Frequency of at risk for pediatric acute respiratory distress syndrome was 3.8% (95% CI, 3.4–5.2%) among the 8, 122 critically ill children who were screened and 5.8% (95% CI, 5.2–6.4%) among the 5, 334 screened children on positive pressure ventilation or high-flow oxygen. Among the 310 at-risk children, median age was 2.1 years (interquartile range, 0.5–7.3 yr). Sixty-six children (21.3%) were subsequently diagnosed with pediatric acute respiratory distress syndrome, a median of 22.6 hours (interquartile range, 9.8–41.0 hr) later. Subsequent pediatric acute respiratory distress syndrome was associated with increased mortality (21.2% vs 3.3%; p < 0.001) and longer durations of invasive ventilation and PICU care. Subsequent pediatric acute respiratory distress syndrome rate did not differ by respiratory support modality at the time of meeting at risk criteria but was independently associated with lower initial saturation:Fio 2 ratio, progressive tachycardia, and early diuretic administration. CONCLUSIONS: The Pediatric Acute Lung Injury Consensus Conference "at-risk for pediatric acute respiratory distress syndrome" criteria identify critically ill children at high risk of pediatric acute respiratory distress syndrome and poor outcomes. Interventional trials aimed at pediatric acute respiratory distress syndrome prevention should target patients early in their illness course and include patients on high-flow oxygen and positive pressure ventilation.